Liquidity premium and stock returns: An empirical study based on samples from U.K. stock market - Lan, Y (2009)
Various empirical studies using different liquidity measures have shown strong evidence of liquidity premium, especially on the US stock market. In comparison, there are rarely any empirical studies based on UK data. Thus, the illiquidity effect on UK stock returns and the corresponding liquidity premium on UK stock market are not clear. In this study, two common liquidity measures are used. One is the bid-ask spread, which proxies the transaction cost dimension of liquidity. Another is turnover rate, proxies the trading quantity dimension. By using these two liquidity proxies, I intend to test whether the UK stock market exhibits a liquidity premium over the 16 years period from January1993 to December 2008. In the cross-sectional analysis, the two liquidity measures are also tested after controlling for the famous size and book-to-market effects. Results from both the portfolio and cross-sectional analysis is consistent, there is no significant signs of liquidity premium on UK stock market using the two proxies. In addition, although this is not the focus of this study, the book-to-market ratio is found to be significant in explaining the cross-section of stock returns on UK stock market after controlling for bid-ask spread, turnover and size.